The endophytic fungi Metarhizium, Pochonia, and Trichoderma, improve salt tolerance in hemp (Cannabis sativa L.) - Shasha Hu; Michael J. Bidochka (PLoS ONE, 2025)
Colonization of plants by fungal endophytes can improve plant growth and can assist in adaptation to biotic and abiotic stresses. The fungal endophytes Metarhizium robertsii and Pochonia chlamydosporia were previously shown to improve hemp growth. Here, the impact of three fungal endophytes, M. robertsii, P. chlamydosporia as well as Trichoderma harzianum on hemp was investigated under treatment with 300 mM NaCl as a salinity stress and reduced watering volume as a drought stress. Plant growth parameters, a lipid oxidation indicator, leaf porphyrins together with the abiotic stress responses genes were assessed in hemp with or without fungal colonization under normal and stressed conditions. Under salinity stress, the growth of hemp was ameliorated by the application of Metarhizium, Pochonia, or Trichoderma in the soil. The increased production of malondialdehyde (MDA) and the reduction in porphyrins in hemp under salinity stress were restored in the presence of fungal endophytes. Under drought stress, the aboveground growth of hemp was recovered by the application of Metarhizium together with the reduced production of porphyrins. The stress related gene CsNAC3 showed decreased expression during fungal application compared with uninoculated hemp under salinity or drought treatment. Colonization of Metarhizium, Pochonia or Trichoderma improved salt stress tolerance in hemp and this was accompanied by a reduction in oxidative stress.